Chemical profile and antimicrobial activity of Secondatia floribunda A. DC (Apocynaceae) - Daiany Alves Ribeiro; Sarah Soares Damasceno; Aline Augusti Boligon; Irwin Rose Alencar de Menezes; Marta Maria de Almeida Souza; José Galberto Martins da Costa (Asian Pacific Journal of Tropical Biomedicine, 2017)
Objective: To establish the chemical profile, and to evaluate the antibacterial and modulatory activity of the ethanolic extracts of the stalk's inner bark and heartwood of Secondatia floribunda. Methods: Quantification of total phenols and flavonoids was determined by the Folin-Ciocalteu method and aluminum chloride, respectively. Phenolic compounds were identified and quantified by HPLC-DAD (High Performance Liquid Chromatography-Diodearray Detector) and the Infrared Spectroscopy was performed using the measure by Attenuated Total Reflectance with Fourier Transform (ATR-FTIR). Antibacterial assays for determination of the Minimum Inhibitory Concentration (MIC) and modification of aminoglycosides were performed by microdilution. Results: Infrared spectra showed similar characteristics, having among its main absorption bands hydroxyl group (OH). The antibacterial activity showed clinically significant results for the strains of Staphylococcus aureus and Escherichia coli. In modulation assay, synergic and antagonistic effect for both extracts was observed. Heartwood extract in combination with antibiotics showed a significant MIC reduction at 19.8% (P < 0.000 1)-79.3% (P < 0.01). Conclusions: This study is the first report of chemical and biological information of Secondatia floribunda suggesting that it is clinically relevant source of a new antibacterial therapy, especially due to the presence of significant levels of phenolic compounds.